2007
DOI: 10.1097/01.prs.0000287133.43718.89
|View full text |Cite
|
Sign up to set email alerts
|

Self-Inducing Shape Memory Geometric Cues Embedded within Smart Hydroxyapatite-Based Biomimetic Matrices

Abstract: Self-induced bone has been achieved via the deployment of osteogenic molecular signals expressed by differentiating osteoblastic-like cells, later secreted and embedded into the smart concavities of the biomimetic matrices. The described biomimetic matrices induce de novo bone formation even in the absence of exogenously applied osteogenic proteins of the TGF-beta superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 33 publications
0
90
0
Order By: Relevance
“…As previously shown using biphasic biomimetic matrices [26], expression of mRNA species is followed by secretion and embedding of the osteogenic gene products, i.e. BMP-7, onto the biomimetic matrices resulting in the induction of bone formation as a secondary response.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As previously shown using biphasic biomimetic matrices [26], expression of mRNA species is followed by secretion and embedding of the osteogenic gene products, i.e. BMP-7, onto the biomimetic matrices resulting in the induction of bone formation as a secondary response.…”
Section: Discussionmentioning
confidence: 90%
“…The induction of bone formation, by combining soluble osteogenic molecular signals with different insoluble signals or substrata, is the essence of the tissue engineering paradigm. This and other studies on the intrinsic osteoinductivity of porous biomimetic matrices are changing the paradigm since the osteogenic signals of the TGF-b superfamily are not previously combined to the biomimetic matrices but rather self-expressed, secreted and embedded into specific geometric configurations of the matrices by differentiating osteoblastic-like cells which attach and differentiate onto the biomimetic substrata [10,11,19,26].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other characteristics such as carrier configurations, connectivity, pore size, and porosity also need to be considered. 34,95 To date, delivery systems have mainly been fabricated in diverse geometries such as three-dimensional matrices/scaffolds, injectable gels, micro/nanoparticulates, films and composites, and are basically classified as: [16][17][18][19]24,87,88,90,169,170 * reservoir systems; * environmentally responsive systems; * biologically inspired systems.…”
Section: Growth Factor Delivery Systems and Devicesmentioning
confidence: 99%
“…According to literature, the geometry of the grafting material could represent a differentiating key-factor able to influence the clinical outcomes. In fact, several studies demonstrated that the surface geometry is a critical factor for cell adhesion and differentiation (9,10). In the light of these chemical and physical features, biomaterials with a surface geometry similar to human bone represent the last generation of synthetic devices.…”
Section: Introductionmentioning
confidence: 99%